The effect of service quality and brand image on customer loyalty with consumer satisfaction as a mediation variable in shopee e commerce - Herman, Hendri; E Janrosl, Viola Syukrina; Aslan, Imran (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to analyze the effect of service quality and brand image on customer loyalty on the Shopee e-commerce platform, by considering consumer satisfaction as a moderating variable. This study uses a survey method using a questionnaire distributed to active Shopee customers who have made transactions carried out in January-June 2023. The research sample was taken by purposive sampling involving 250 respondents. Data analysis was carried out using multiple regression analysis and data was processed using Smart PLS 3. The results of this study show that service quality has a significant positive effect on Shopee customer loyalty. In addition, brand image also has a significant positive influence on customer loyalty. This finding shows that the quality of service and Shopee's brand image are important factors in building customer loyalty. Furthermore, consumer satisfaction has also proven to be a significant moderating variable in the relationship between service quality brand image, and customer loyalty. Service quality has a positive and significant influence on customer loyalty through customer satisfaction. Customer satisfaction is a key factor in building customer loyalty, and good service quality can increase the level of customer satisfaction. When customers receive good services, such as prompt responses, effective assistance, and timely delivery, they will have a positive experience.